Transitions towards car-free cities - van Waas, Willem (Student Undergraduate Research E-journal!, 2018)
As various cities around the world are implementing car-free policy, the need to understand it from a dynamic point of view becomes more pronounced. This paper sheds more light on the reasons to go car-free as forces of change, while further analyzing the inhibitors and dynamics of transitions towards car-free cities. Reasons to drive can be conceptualized as intrinsic and extrinsic, each with its own relevance in the light of transitions. At the same time, the dynamic processes of enabling and implementation are conceptualized in order to move towards a more realistic view of the complexities of these transitions.